Integrated optical LiNbO3 distributed polarisation mode dispersion compensator in 20Gbit/s transmission system - Noé, Reinhold; Sandel, D; Hinz, S; Yoshida-Dierolf, M; Mirvoda, V; Feise, G; Herrmann, H; Ricken, R; Sohler, W; Wehrmann, F; Glingener, C; Schopflin, A; et al. (ELECTRONICS LETTERS)

Polarization mode dispersion compensation at 10, 20, and 40 Gb/s with various optical equalizers - Noé, Reinhold; Sandel, D; Yoshida-Dierolf, M; Hinz, S; Mirvoda, V; Schopflin, A; Glingener, C; Gottwald, E; Scheerer, C; Fischer, G; Weyrauch, T; Haase, W (JOURNAL OF LIGHTWAVE TECHNOLOGY)

Multistage spectral polarimeter based on integrated acoustooptical Ti : LiNbO3 TE-TM converters for WDM system monitoring - Noé, Reinhold; Maucher, A; Ricken, R (SELECTED PAPERS FROM PHOTONICS INDIA ‘98)

Longitudinal structure characterization of fiber Bragg gratings by optical network analysis - Sandel, D; Noé, Reinhold (SELECTED PAPERS FROM PHOTONICS INDIA ‘98)

Integrated-optical polarization mode dispersion compensation for 6-ps, 40-Gb/s pulses - Sandel, D; Hinz, S; Yoshida-Dierolf, M; Mirvoda, V; Noé, Reinhold; Feise, G; Herrmann, H; Ricken, R; Sohler, W; Suche, H; Wehrmann, F; Wessel, R (ECIO’99: 9TH EUROPEAN CONFERENCE ON INTEGRATED OPTICS AND TECHNICAL EXHIBITION)

Spectral polarimeters based on integrated acousto-optical Ti : LiNbO3 TE-TM converters - Noé, Reinhold; Maucher, A; Ricken, R (FIBER AND INTEGRATED OPTICS)

Proposal of distributed polarization mode dispersion compensator in LiNbO3 - Sandel, D; Noé, Reinhold (ECIO’99: 9TH EUROPEAN CONFERENCE ON INTEGRATED OPTICS AND TECHNICAL EXHIBITION)

Polarisation mode dispersion compensation for 6ps, 40Gbit/s pulses using distributed equaliser in LiNbO3 - Hinz, S; Sandel, D; Yoshida-Dierolf, M; Mirvoda, V; Noé, Reinhold; Feise, G; Herrmann, H; Ricken, R; Sohler, W; Suche, H; Wehrmann, F; Wessel, R (ELECTRONICS LETTERS)

Integrated optical LiNbO3 distributed polarisation mode dispersion compensator in 20Gbit/s transmission system - Noé, Reinhold; Sandel, D; Hinz, S; Yoshida-Dierolf, M; Mirvoda, V; Feise, G; Herrmann, H; Ricken, R; Sohler, W; Wehrmann, F; Glingener, C; Schopflin, A; et al. (ELECTRONICS LETTERS)

Polarization mode dispersion compensation at 10, 20, and 40 Gb/s with various optical equalizers - Noé, Reinhold; Sandel, D; Yoshida-Dierolf, M; Hinz, S; Mirvoda, V; Schopflin, A; Glingener, C; Gottwald, E; Scheerer, C; Fischer, G; Weyrauch, T; Haase, W (JOURNAL OF LIGHTWAVE TECHNOLOGY)

10-Gb/s PMD compensation using ferroelectric liquid crystals and several PMD penalty signals - Hinz, S; Sandel, D; Yoshida-Dierolf, R; Mirvoda, V; Noé, Reinhold; Weyrauch, T; Beresnev, L; Haase, W (SELECTED PAPERS FROM PHOTONICS INDIA ‘98)

Wissenbasierte Konzepte und visuelle interaktive Systeme - Dücker, M.; Flake, Stephan; Geiger, C.; Müller, Wolfgang; Paelke, Volker; Reimann, C.; Rosenbach, W.; Zimmermann, D.; Zelder, S.
Dieser Beitrag stellt eine Auswahl aktueller Arbeiten des C-LAB Instituts in Paderborn vor, die sich im wesentlichen in der Schnittmenge der Anwendung wissensbasierter Techniken im Systementwurf und dem Design interaktiver visueller Sy- steme ansiedeln. Der allgemeinen Ausrichtung des C-LABs folgend, haben die meisten Projekte einen stark anwendungsbe- zogenen Charakter. Der Beitrag gibt einen kurzen Überblick der wichtigsten aktuellen Arbeiten in diesem Bereich („Breite vor Tiefe“) und skizziert die zukünftigen F&E-Aktivitäten, die sich auf die Anwendung wissensbasierter Konzepte beim Entwurf interaktiver visueller Systeme konzentrieren.

Generation of Interactive Visual Environments for Direct Manipulation of Database Content - Dangberg, Andreas; Müller, Wolfgang (Proceedings of the IEEE Symposium on Visual Languages)

Agent-Based Modeling for Holonic Manufacturing Systems with Fuzzy Control - Flake, Stephan; Geiger, Christian; Lehrenfeld, G.; Müller, Wolfgang; Paelke, Volker (Proceedings of NAFIPS'99, 18th International Conference of the North American Fuzzy Information Processing Society)
Agent-based systems technologies are of emerging interest in the specification and implementation of complex systems. This article introduces the CASA agent development system which seamlessly combines the BDI (belief desire intention) approach with the FIPA agent communication language standard and an integrated specification of fuzzy controllers. The behavior of agents is defined by strategies which basically correspond to extended guarded Horn clauses with priorities. The presented concepts are introduced by an example from computer integrated manufacturing (CIM). The example gives the specification of a fuzzy controller for a manufacturing station in the context of a holonic manufacturing system (HMS).
Keywords: Manufacturing systems; Fuzzy control; Multiagent systems; Control systems; Concurrent computing; Specification languages; Communication standards; Standards development; Communication system control; Computer integrated manufacturing

Scalable System for 3D Audio Raytracing - Müller, Wolfgang; Ullmann, F. (Proceedings IEEE International Conference on Multimedia Computing and Systems)
Though several approaches in sound processing are denoted as 3D audio very few of them generate high quality 3D audio information which allows listeners to exactly locate sound sources in three dimensional space. We present an approach to enhance sound by high quality 3D audio information through acoustic ray tracing where 3D audio is offline processed with digital filters of a head-related transfer function. The basic approach computes a fixed sound source for fixed listener. This approach is extended to generate 3D audio for moving listeners in interactive environments.
Keywords: Ray tracing; Loudspeakers; Motion pictures; Acoustic reflection; Ear; Digital filters; Parallel processing; Humans; Physics; Crosstalk

‘Böse Blicke’ – Der Gesellschaftsroman nach 1945 (komparatistisch) - Morrien, Rita (Frauen Literatur Geschichte)

Spectral polarimeters based on integrated acousto-optical Ti : LiNbO3 TE-TM converters - Noé, Reinhold; Maucher, A; Ricken, R (FIBER AND INTEGRATED OPTICS)

Integrated-optical polarization mode dispersion compensation for 6-ps, 40-Gb/s pulses - Sandel, D; Hinz, S; Yoshida-Dierolf, M; Mirvoda, V; Noé, Reinhold; Feise, G; Herrmann, H; Ricken, R; Sohler, W; Suche, H; Wehrmann, F; Wessel, R (ECIO’99: 9TH EUROPEAN CONFERENCE ON INTEGRATED OPTICS AND TECHNICAL EXHIBITION)

Proposal of distributed polarization mode dispersion compensator in LiNbO3 - Sandel, D; Noé, Reinhold (ECIO’99: 9TH EUROPEAN CONFERENCE ON INTEGRATED OPTICS AND TECHNICAL EXHIBITION)

Metallomesogens presenting blue phases in a glassy state and in metallomesogen/nematic mixtures - Buey, Julio; Espinet, Pablo; Kitzerow, Heinz-Siegfried; Strauss, Jochen (Chemical Communications)
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis